Political participation and ethnic minorities : Chinese overseas in Malaysia, Indonesia, and the United States - Freedman, Amy L. (New York : Routledge, 2000)
Annotation Amy Freedman's empirical study examines the hows and whys of Chinese overseas political activity in three diverse countries.
1. Introduction -- 2. Theoretical Approaches to Understanding Political Participation and Influence -- 3. Malaysia: Institutionalized Participation -- 4. Suharto's Indonesia: Outsiders Tied to the Palace -- 5. Chinese in the United States -- 6. Suburbanization: Chinese in Monterey Park, California -- 7. New York: The City of Ethnic Politics -- 8. Conclusion.
Includes bibliographical references (pages 209-222) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Chinese -- Foreign countries -- Politics and government; Chinese -- Southeast Asia; Chinese -- United States; Minorities -- Political activity; Chinois -- Asie du Sud-Est.; Minorités -- Activité politique; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Chinese; Minorities -- Political activity; Southeast Asia; United States